Dental students’ perceptions on preclinical restorative dentistry course: Biruni University case - Ayar, Muhammet Kerim (The European Research Journal, 2018)
Objectives. The student’s perspectives of their restorative dentistry education would be an important source of information for evaluation of preclinical curriculum. Thus, the aim of the present research was to obtain information from second-year students at Biruni University dental school about their preclinical restorative dentistry program perceptions, levels of stress during preclinical courses and preparedness for upcoming restorative dentistry courses in clinics.Methods. The present survey was carried out on the second year students in dental school in Istanbul. The survey composed of items regarding students’ perspectives regarding to the levels of their stress in preclinical restorative dentistry courses as well as preparedness for future restorative dentistry courses in clinic. Student’s t-test was applied to the data.Results. Students found posterior composite restorations lessons more stress-full than amalgam restoration lessons. They expressed that knowledge they obtained from the lectures is adequate for preclinical courses and they felt themselves prepared for the restoration of posterior teeth in clinic.Conclusions. Second-year student’s perceptions of preclinical restorative dentistry curriculum in Biruni University were highly positive. The student’s perspectives of their restorative dentistry curriculum would be an important source of information for dental faculty staff in order to establish an adequate preclinical curriculum for the students who start delivering public patient care in the future.